PENGARUH PERAN PEMBIAYAAN MUDHARABAH TERHADAP PERKEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) DI BNI SYARIAH CABANG MEDAN - Nailul Maulidatul Barakah (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2021)
Mudharabah financing is one of the products that is in great demand by the public, especially MSME actors, this is because through mudharabah financing it can develop the business results of MSMEs in the community, but in this study the authors saw that mudharabah financing during the last five years had decreased. It is interesting for the author to see the relevance of the influence of mudharabah financing on the development of Micro, Small and Medium Enterprises. Based on the problems above, the researcher wants to know more about